Comparative Efficacy of Intranasal Midazolam with per Rectal Diazepam to Control Acute Seizure in 6 months to 12 years’ Children (Journal of National Institute of Neurosciences Bangladesh, 2024)
Background: Convulsions are the most frequent neurological disorders affecting children. Acute seizure is a medical emergency, requires prompt and urgent control of ongoing seizure activity. Among the procedure to control seizure, treatment options like intranasal midazolam and per rectal diazepam are available for immediate management.Objective: The study was done to compare the safety and efficacy of intranasal midazolam and per rectal diazepam to control acute seizure.Method: This randomized controlled trial was conducted in paediatric department of Dhaka Medical College Hospital from 1st June 2008 to 15th April 2009.Children aged from 6 month to 12 years who came with acute seizure of any aetiology were included.Result: Among 110 patients mean time to control acute seizure in diazepam group was 4.1 minute and in midazolam group it was 3.2 minute and the difference was statistically significant. No significant side effects were noted in either of the group except for a transient fall in oxygen saturation.Conclusion:In this study midazolam effectively controlled acute seizure compared to diazepam. Time taken to control seizure was significantly less in midazolam group. No serious complications were noted after administration of drugs. Intranasal midazolam could be a better alternative as it is effective in controlling seizure and has no significant side effects compared to the standard.Journal of National Institute of Neurosciences Bangladesh, July 2023;9(2):103-107